Analgesic step ladder treatment in cancer patients with pain - Kursun, Yucel Zulfi; Yildiz, Fuat; Kaymaz, Omer; Onal, Selami Ates (Kare Publ, 2015)
Objectives: In this study, we retrospectively evaluated the characteristics of 1736 patients presenting to our clinic, including analgesic step treatments and method of treatments. Methods: A total of 1467 patients, excluding 269 out of 1736, with pain due to malignancy were included in this study. Patients presented to the Algology Division of the Department of Anesthesiology and Reanimation of Firat University School of Medicine. Among the patients included in the study, 85.5% were treated according to the analgesic step ladder protocol of the WHO. Minimally invasive analgesic interventions were applied in 14.5% of the cases in which adequate pain control could not be achieved with step ladder treatment. Results: The adjuvant pain medications used were antidepressants, corticosteroids, anticonvulsants, neuroleptics, benzodiazepines, local anesthetics, bisphosphonates, and calcitonin and their rate of usage were 61.0%, 7.1%, 4.0%, 4.0%, 1.6%, 12.3%, 1.2%, and 2.8%, respectively. Conclusion: Because pain in the cancer patients is mostly severe, pain management can be difficult in these patients. The patients who cannot be treated with the analgesic step ladder method have been treated with minimally invasive analgesic intervention methods. A multidisciplinary medical expert group evaluation of the cases and a treatment planned by this team are cornerstones of achieving success in pain management. We believe in this way, no patient with cancer will live with uncontrolled pain. Access to adjuvant drugs should be easy in order to achieve success in pain management. We believe that expert algology physicians who treat pain should easily prescribe adjuvant drugs.
Agrili kanser hastalarinin tedavisinde analjezik basamak tedavisinin yeri
Keywords: Adjuvants; analgesic step ladder treatment; cancer pain; minimally invasive analgesic procedure; opioid